Inclusion Results on Hypergeometric Functions in a Class of Analytic Functions Associated with Linear Operators (Contemporary Mathematics, 2024)
This study focuses on analyzing the inclusion properties of a certain subclass of analytic functions. This study examines the Hohlov integral transform, which is associated with the normalized Gaussian hypergeometric function, and the Komatu integral operator, which is associated with the generalized polylogarithm. The investigation utilizes Taylor coefficients to analyze these analytic functions. Various results are obtained for these operators for specific values of the parameters. The results presented here include several previously known results as their special cases.
Keywords: Gaussian hypergeometric functions, starlike functions, convex functions, Hohlov integral transform, Komatu integral operator